Energetic consequences of walking like an inverted pendulum: Step-to-step transitions - Kuo, A. D.; Donelan, J. M.; Ruina, A. (Exercise and Sport Sciences Reviews, 2005)
Walking like an inverted pendulum reduces muscle-force and work demands during single support, but it also unavoidably requires mechanical work to redirect the body's center of mass in the transition between steps, when one pendular motion is substituted by the next. Production of this work exacts a proportional metabolic cost that is a major determinant of the overall cost of walking.